311 CORONARY CT ANGIOGRAPHY A NEW PROMISING TOOL IN HEART TRANSPLANTED PATIENTS: FROM CLINICAL AND ECONOMICAL BENEFITS TO CORONARY INFLAMMATION DETECTION. (15th December 2022) - Dellino, Carlo Maria; Pergola, Valeria; Scarpa, Francesco; Storer, Vittorio; Galzerano, Domenico; Tessari, Chiara; Fraiese, Angela; Motta, Raffaella; Gerosa, Gino; Iliceto, Sabino; Mele, Donato
Abstract: Background: Heart transplanted patients are mainly monitored with invasive diagnostic techniques for detecting cardiac allograft vasculopathy (CAV). However coronary CT angiography (CCTA) is a new promising tool that brings clinical and economical benefits. Objectives: primary aim: demonstrate the non-inferiority of CCTA in comparison to invasive coronary angiography (ICA), in terms of radiation and contrast dose, costs, in-hospital stay and complications. Other aims: analyse in the subgroup of patients undergoing CCTA the role of immunological and non-immunological risk factors and the role of pericoronary-fat-attenuation-index (pFAI) in predicting CAV. Methods: Between March 2021 and May 2022, 179 consecutive heart transplanted patients underwent either CCTA (78 patients) or ICA (101 patients) based on medical preference to study CAV. The 78 patients who underwent CCTA were also divided in patients with no previous CAV (npCAV, previous ISHLTV=0) and patients with previous CAV (pCAV, ISHLTV≤1). CAV progression was considered if there was any progression in ISHLTV. Results: CCTA delivered lower radiation doses in comparison with ICA (3, 52 mSV [1.46-7.23] versus 10, 8 mSV [8.8-20.3]; p=0.03) and required also less in-hospital stay (0.5 ± 0, 2 hours versus 23.7 ± 12.31 hours; p<0.001), lower costs (120 euros versus 2800 euros; p<0.001) and less contrast agent (60.4 ± 8.7 ml versus 95.68 ± 47.6ml; p<0.001). The rate of complications of CCTA and ICA was low in both of them (0 (0%) vs 3 (3%); p=0, 258). Among the non-immunological risk factors for CAV, only smoking was related with the progression of CAV (0% with ISHLTV=0 and 15% with ISHLTV 1; p=0.015). Among immunological risk factors, TNF was the only independent predictor in the progression of CAV (HR 8.23; IC 95% 1.47-45.81; p=0.019). PFAI either as a continuous variable or as a categorical variable (>-70.1HU) did not show a statistically significance in the progression of CAV (p=NS). Conclusions: CCTA is superior to ICA in terms of radiation and contrast dose, costs and in-hospital stay. TNF was the only independent predictor related with the progression of CAV. PFAI, didn't reach statistically significance probably due to the small sample size. Further studies are necessary to understand the role of pFAI in this subset of patients.